Keakuratan FNAB pada Limfadenitis Tuberkulosis di Kelenjar Getah Bening Leher di Manado - Ijong, Jessie I.; Lumintang, Nico (e-CliniC, 2024)
Abstract: Tuberculous lymphadenitis is the most common type of extrapulmonary tuberculosis (TB). Fine needle biopsy aspiration (FNAB) is an initial diagnostic method to evaluate lymph node enlargement in the neck This study aimed to evaluate the accuracy of FNAB in tuberculous lymphadenitis in neck lymph nodes in Manado. This was is a retrospective and descriptive study using medical record data on the use of FNAB examination in patient with a history of lymph node enlargement years 2017-2018. The results obtained 160 FNAB samples with clinical lymph node enlargement in the neck; 86 samples (54%) with TB lymphadenitis, nine samples (6%) were suspected as TB lymphadenitis, and 65 samples (40%) were not TB lymphadenitis The incidence in women (61%) was higher than in men (39%). TB lymphadenitis was most common in women aged <19 years and men aged 20-30 years. In conclusion, FNAB remains an important option as one of the diagnostic supporting tools for lymph node enlargement especially to confirm the diagnosis of tuberculous lymphadenitis in the neck. Keywords: fine needle biopsy aspiration; tuberculous lymphadenitis; cytopathological diagnosis   Abstrak: Limfadenitis tuberkulosis (TB) merupakan bentuk TB ekstrapulmoner yang tersering. Fine needle biopsy aspiration (FNAB) ialah metode diagnostik awal untuk mengevaluasi pembesaran kelenjar getah bening di leher. Penelitian ini bertujuan untuk mengetahui keakuratan FNAB pada limfadenitis tuberkulosis di kelenjar getah bening leher di Manado. Jenis penelitian ialah deskriptif retrospektif menggunakan data rekam medik penggunaan pemeriksaan FNAB pada pasien yang memiliki riwayat pembesaran kelenjar getah bening di leher di Laboratorium Patologi Anatomi RSUP Prof R. D. Kandou Manado.tahun 2017-2018. Hasil penelitian mendapatkan 160 sampel FNAB dengan klinis pembesaran pada leher; 86 sampel (54%) dengan hasil FNAB limfadenitis TB, sembilan sampel (6%) dicurigai sebagai limfadenitis TB, dan 65 sampel (40%) bukan limfadenitis TB. Kejadian pada perempuan (61%) lebih tinggi daripada laki-laki (39%). Limfadenitis TB tersering pada perempuan berusia <19 tahun dan laki-laki 20-30 tahun. Simpulan penelitian ini ialah sampai saat ini FNAB tetap menjadi pilihan sebagai salah satu alat penunjang diagnostik untuk evaluasi pembesaran kelenjar getah bening terutama dalam menentukan limfadenitis TB di leher. Kata kunci: fine needle biopsy aspiration; limfadenitisis tuberculosis; diagnostik sitopatologi